Analysis of kidney transplants in brazil: a comparative study pre and post-COVID-19 pandemic - Santos, Thainá B.; de Oliveira, Brenda E. S.; Bispo, Emilie V.; Filho, Paulo J. R. de A. Coutinho; Pereira, Thiago S. C.; e Silva, Victor H. B. G.; Passarinho, Camila G. C. (International Journal Of Community Medicine And Public Health, 2025)
Background: Kidney transplantation is essential for patients with advanced Chronic Kidney Disease (CKD), a condition that affects 13% of the global population. Although Brazil stands out internationally, ranking fourth worldwide in kidney transplants, the COVID-19 pandemic posed significant challenges. The restructuring of the healthcare system and restrictions led to a reduction in transplants by up to 50% globally and 32% in Brazil, exacerbating disparities in access to the procedure. Methods: It is an ecological study based on data from the Brazilian Transplant Registry (RBT), which examined the evolution of kidney transplants in Brazil across the pre-pandemic (2018-2019), pandemic (2020-2022), and post-pandemic (2023) periods. Results: Between 2018 and 2023, a total of 33,224 kidney transplants were performed in Brazil, with a significant decline during the pandemic (-18.8% annual average) but a partial recovery in 2023 (18.2% of the total). The waiting list increased by 175.8%, with a 104.9% rise in the number of untreated patients. The productivity of medical teams dropped from 43 to 34 transplants per team during the pandemic, and deceased donors predominated (85.7%). Regionally, the Southeast accounted for the highest number of procedures, with São Paulo responsible for 32.6% of the transplants, highlighting inequalities in access to treatment. Conclusions: Finally, it is observed that the COVID-19 pandemic negatively impacted kidney transplants in the country due to the reorganization of hospital care, with a gradual post-pandemic recovery, although still below pre-crisis levels.